Compound sawtooth in EAST LHCD plasma： An experimental study - Xu, Li-Qing; Hu, Li-Qun; Chen, Kai-Yun; Li, Miao-Hui (Chinese physics B, 2014)
A compound sawtooth with an incomplete relaxation was observed in EAST＇s lower hybrid current drive （LHCD） plasma. The sub-crash phase of the compound sawtooth corresponds to a longer-lasting and slower-growing 1/1 mode. Based on the two-dimensional （2D） SXR tomography, the time-dependent 2D image of a compound sawtooth crash is obtained. The island produced during a resistive internal kink mode is observed in the all crash phases of the compound sawtooth. The destabilization of 1/I long-lasting saturated 1/1 mode is related to the current driven by the LHCD near the q = 1 surface.